Biosynthesis and antibacterial activity of silver nanoparticles using Flos Sophorae Immaturus extract. Issue 8 (August 2022) - Cheng, Zhong; Tang, ShanWen; Feng, Jing; Wu, Yu
Abstract: The current study proposes a green synthesis method for silver nanoparticles (Ag NPs) using various concentrations of Flos Sophorae Immaturus extract as reducing and capping agents. The UV-Visible (UV-Vis) spectroscopy, X-ray Diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), X-ray Photoelectron Spectroscopy (XPS), Dynamic Light Scattering (DLS) and Transmission Electron Microscopy (TEM) were used to characterize resulting brown nanopowder. The as-prepared Ag NPs had a high negative zeta potential value of ∼ -38 mv, indicating the existence of electrostatic stabilization. The average sizes of ∼27.8 nm, 28.5 nm, 34.3 nm and 36.5 nm were measured by TEM. Moreover, FTIR and XPS analyses validated the production and chemical composition of Ag NPs from silver nitrate. The antibacterial activity of Ag NPs was examined against E. coli, P. aeruginosa, and S. aureus using agar well diffusion and the minimum inhibitory concentration (MIC) method. The antibacterial activity of the as-prepared Ag NPs from 4 mL extract was excellent against E. coli, P. aeruginosa, and S. aureus and the MIC values were 31.250, 15.625, and 31.250 mg/L, respectively. Based on these results, this study proposes a practical approach for the synthesis of Ag NPs in the industry and medical fields. Abstract : Biosynthesis; Flos sophorae immaturus extract; Ag NPs; Nanotechnology; Bacteria; Antibacterial activity.